SARS-CoV-2 infection decreases cardiorespiratory fitness and time-trial performance even two months after returning to regular training — Insights from a longitudinal case series of well-trained kayak athletes - Deng, S.; Yin, M.; Chen, Z.; Deng, J.; Wang, Z.; Li, Y.; Lyu, M.; Zhang, B.; Zhu, S.; Hu, S.; Nassis, G. P.; Li, Y. (Journal of Exercise Science & Fitness, 2024)
Objective The aims of this study were to examine the effect of SARS-CoV-2 infection on cardiorespiratory fitness (CRF) and time-trial performance in vaccinated well-trained young kayak athletes.